3,4-Diaminopyridine induced stimulus-bound repetitive firing in frog sympathetic ganglion: no changes in postsynaptic membrane excitability - Vlcková, E; Stolc, S (Physiologia Bohemoslovaca, 1990)
It has been shown previously that 3,4-diaminopyridine (3,4-DAP) facilitates synaptic transmission in the frog sympathetic ganglion inducing so-called stimulus-bound repetition (SBR), i.e. a brief burst of repetitive postganglionic discharges after a single orthodromic stimulus. In the present study we analyzed one of the possible mechanisms of the 3,4-DAP-induced SBR, namely changes in postsynaptic membrane excitability. We found that 3,4-DAP in concentration optimal for inducing SBR (2 X 10(-4) mol.l-1) had no direct effect on the excitability of the postsynaptic membrane of frog sympathetic neurones. The excitability was expressed as the threshold for action potentials elicited orthodromically, antidromically and directly, as well as the spike activity evoked by constant depolarizing current pulses. We also indirectly excluded the involvement of two other possible mechanisms of neuronal membrane excitability modulation in the 3,4-DAP-induced SBR, i.e. the M-current suppression by analyzing the participation of muscarinic receptor activation in the SBR, and inhibition of the Ca(2+)-activated K+ currents by measuring the duration of afterhyperpolarization of antidromic action potential. Our findings indicate that no remarkable changes in the properties of the postsynaptic membrane contribute to the generation of 3,4-DAP-induced SBR in the frog sympathetic ganglion. This strongly supports the hypothesis that the mechanism underlying SBR evoked by this drug is presynaptic.
Keywords: akční potenciály; Rana esculenta; Action Potentials; Amifampridine; Synaptic Transmission; 4-aminopyridin; Synaptic Membranes; nervový přenos; 4-Aminopyridine; amifampridin; Animals; sympatická ganglia; synaptické membrány; Potassium Channels; Rana temporaria; draslíkové kanály; Ganglia, Sympathetic; zvířata